La cosificació de les normes d'ús lingüístic. Aspectes sociològics d'un discurs distorsionat - Calaforra, Guillem (Caplletra. Revista Internacional de Filologia, 1996)
The subject matter of sociolinguistics are the rules or patterns of the functioning of language. But rules and transgressions are complementary facts, and sociolinguists must study both conventional and intentional language use (that is, traditional and meaningful social actions). When sociolinguistics deals exclusively with norms, but ne t with transgressions, sociolinguists reify a socially constructed reality. By applying the concept of reification, we consider that sociolinguists confuse rules, laws and regularities; therefore, more interpretation is needed to complement explanation, and it seems that sociolinguistics needs more «research programmes» studying the importance of individuals and individual meaningful action in sociolinguistic structures.